Effects of Computer Assisted Instruction on Knowledge of Injection Administration and Medication Calculation of Pediatric Nurses - ชัยลี กรรณิการ์; ธรรมพนิชวัฒน์ วัลยา; พยัคฆเรือง สุดาภรณ์ (Journal of The Royal Thai Army Nurses, 2020)
This quasi-experimental study (one group pre-test post-test design) aimed to determine the effects of Computer Assisted Instruction (CAI) on knowledge of injection administration and medication calculation of pediatric nurses. The sample included 21 registered nurses who had a working experience of less than 1 year from inpatient wards of Queen Sirikit National Institute of Child Health and inpatient pediatric wards of Vajira Hospital, Faculty of Medicine, Navamindradhiraj University. The subjects got CAI in a compact disk. They were asked to study CAI by themselves for 14 days. They were also asked to record the information each time they viewed CAI, including the title, number of times, date and time in a table of learning log. On the 7th day, the researcher called the subjects to ask about the problems in using CAI, reminded and encouraged them. The Assessment of Knowledge of Injection Administration and Test of Medication Calculation were used to assess the subjects’ knowledge before and after learning from CAI for 2 weeks. Descriptive statistics and Wilcoxon signed-rank test were used for data analysis. The findings of the study revealed that after learning from CAI, the subjects had higher scores on knowledge of injection administration and knowledge of medication calculation than those before learning from CAI with statistical significance (p < .05). It is suggested that CAI may be used to teach newly graduated nurses through self-directed learning about knowledge of injection administration and medication calculation in care of pediatric patients.